2015
DOI: 10.3923/ajcs.2015.186.196
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Application of Ascorbic Acid Ameliorates Detrimental Effects of Salt Stress in Rice (MRQ74 and MR269) Seedlings

Abstract: An in vitro investigation was conducted to evaluate the potential role of exogenously applied ascorbic acid in alleviating the effect of sodium chloride (NaCl) in two varieties of rice, Oryza sativa L. (MRQ74 and MR269), that differ in salt tolerance susceptibility. Seven-day-old rice seedlings germinated on Murashige and Skooge (MS) medium were transferred to MS media containing (200 mM) NaCl and (0, 0.5, 1, 1.5 mM) ascorbic acid for 14 days. The results showed that both varieties of seedling, when exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…2 ). This increase in plant growth could attribute with the physiological processes including nutrient uptake, photosynthesis and increasing antioxidant activities as suggested by ( Alhasnawi et al, 2015 ). Our results also showed that the negative impact of soil salinity can overcome by the foliar application of AsA and can increase photosynthetic pigments ( Fig.…”
Section: Discussionmentioning
confidence: 84%
“…2 ). This increase in plant growth could attribute with the physiological processes including nutrient uptake, photosynthesis and increasing antioxidant activities as suggested by ( Alhasnawi et al, 2015 ). Our results also showed that the negative impact of soil salinity can overcome by the foliar application of AsA and can increase photosynthetic pigments ( Fig.…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, the combination of Cr(VI) and MEL further enhanced the polyphenol contents. It has been previously reported that antioxidants produced within plants reduce the effects of stresses in plants [58,59]. Those polyphenols possess the affinity to bind with metal ions and thereby inhibit the production of several ROS and some of them sequester the heavy metals entering the cell [60].…”
Section: Concentrationsmentioning
confidence: 99%
“…. Salt stress in culture media can inhibit callus growth by ion imbalance, ion toxicity, water deficit, or a combination of any of these factors (Alhasnawi et al, 2015;Hosseini et al, 2012). In this context, Younis et al, (2010) reported that growth degradation caused by NaCl is because of the reduction of apical growth in cells, as well as the imbalance of endogenous hormonal growth.…”
Section: Biochemical Estimationmentioning
confidence: 99%